Flow of MHD Carreau Fluid in a Curved Channel - Saima Noreen; Tasawar Hayat; Ahmed Alsaedi (Applied Bionics and Biomechanics)
Analysis has been made for the curvature effects on the MHD peristaltic flow of an incompressible Carreau fluid in a channel. The flow problem is first reduced in the wave frame of reference and then solved after employing the long wavelength and low Reynolds number approximations. Expressions of stream function, pressure gradient, magnetic force function, induced magnetic field and current density are derived and then examined for various parameters of interest.